Dermatologic disorders of the athlete - Adams, B. B. (Sports Medicine, 2002)
The most common injuries afflicting the athlete affect the skin. The list of sports-related dermatoses is vast and includes infections, inflammatory conditions, traumatic entities, environmental encounters, and neoplasms. It is critical that the sports physician recognises common and uncommon skin disorders of the athlete. Knowledge of the treatment and prevention of various sports-related dermatoses results in prompt and appropriate care of the athlete. Infections probably cause the most disruption to individual and team activities. Herpes gladiatorum, tinea corporis gladiatorum, impetigo, and furunculosis are sometimes found in epidemic proportions in athletes. Vigilant surveillance and early treatment help teams avoid these epidemics. Fortunately, several recent studies suggest that pharmacotherapeutic prevention may be effective for some of these sports-related infections. Inflammatory cutaneous conditions may be banal or potentially life threatening as in the case of exercise-induced anaphylaxis. Athletes who develop exercise-induced anaphylaxis may prevent outbreaks by avoiding food before exercise and extreme temperatures while they exercise. Almost all sports enthusiasts are at risk of developing traumatic entities such as nail dystrophies, calluses and blisters. Other more unusual traumatic skin conditions, such as talon noire, jogger's nipples and mogul's palm, occur in specific sports. Several techniques and special clothing exist to help prevent traumatic skin conditions in athletes. Almost all athletes, to some degree, interact with the environment. Winter sport athletes may develop frostbite and swimmers in both fresh and saltwater may develop swimmer's itch or seabather's eruption, respectively. Swimmers with fair skin and light hair may also present with unusual green hair that results from the deposition of copper within the hair. Finally, athletes are at risk of developing both benign and malignant neoplasms. Hockey players, surfers, boxers and football players can develop athlete's nodules. Outdoor sports enthusiasts are at greater risk of developing melanoma and non-melanoma skin cancer. Athletes spend a great deal of time outdoors, typically during peak hours of ultraviolet exposure. The frequent use of sunscreens and protective clothing will decrease the athlete's sun exposure. It is critical that the sports physician recognises common and uncommon skin disorders of the athlete. Knowledge of the treatment and prevention of various sports-related dermatoses results in prompt and appropriate care of the athlete.